GE_GERICHTE C/18752/2016 vom 19. Juni 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; CONJOINT ; ENFANT ; INTERDICTION D'ALIÉNER ; OBLIGATION D'ENTRETIEN | CC.176.al1; CC.178.al1; CC.178; CC.163